A Nanomedicine Fabricated from Gold Nanoparticles‐Decorated Metal–Organic Framework for Cascade Chemo/Chemodynamic Cancer Therapy. Issue 17 (14th June 2020) - Ding, Yuan; Xu, Hao; Xu, Chang; Tong, Zongrui; Zhang, Sitong; Bai, Yang; Chen, Yining; Xu, Qianhui; Zhou, Liuzhi; Ding, Hao; Sun, Zhongquan; Yan, Sheng; et al.
Abstract: The incorporation of new modalities into chemotherapy greatly enhances the anticancer efficacy combining the merits of each treatment, showing promising potentials in clinical translations. Herein, a hybrid nanomedicine (Au/FeMOF@CPT NPs ) is fabricated using metal–organic framework (MOF) nanoparticles and gold nanoparticles (Au NPs) as building blocks for cancer chemo/chemodynamic therapy. MOF NPs are used as vehicles to encapsulate camptothecin (CPT), and the hybridization by Au NPs greatly improves the stability of the nanomedicine in a physiological environment. Triggered by the high concentration of phosphate inside the cancer cells, Au/FeMOF@CPT NPs effectively collapse after internalization, resulting in the complete drug release and activation of the cascade catalytic reactions. The intracellular glucose can be oxidized by Au NPs to produce hydrogen dioxide, which is further utilized as chemical fuel for the Fenton reaction, thus realizing the synergistic anticancer efficacy. Benefitting from the enhanced permeability and retention effect and sophisticated fabrications, the blood circulation time and tumor accumulation of Au/FeMOF@CPT NPs are significantly increased. In vivo results demonstrate that the combination of chemotherapy and chemodynamic therapy effectively suppresses the tumor growth, meantime the systemic toxicity of this nanomedicine is greatly avoided. Abstract : A hybrid nanomedicine (Au/FeMOF@CPT NPs) consisting of metal–organic framework nanoparticles (MOF NPs) and Au NPs is developed for cancer chemo/chemodynamic therapy. MOF NPs are used as vehicles to encapsulate camptothecin (CPT). H2 O2 from the oxidation of intracellular glucose by Au NPs is further utilized as fuel for the Fenton reaction, thus realizing the synergistic anticancer efficacy.